ANALYSIS OF EDUCATIONAL CONTENT AND WORD OF MOUTH ON THE DECISION TO PAY ZAKAT WITH TRUST AS A VARIABLE INTERVENING IN THE NATIONAL ZAKAT COLLECTION INSTITUTION BAITULMAAL MUAMALAT - Budi Syahputra; Mesra B; Muhammad Dharma Tuah Putra Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of educational content and word of mouth on zakat payment decisions with trust as a mediating variable. The study used the Partial Least Squares approach with 85 respondents. The test results show that educational content has a significant effect on trust with a coefficient value of 0.585 and a direct effect on zakat payment decisions with a coefficient value of 0.448. Word of mouth also has a significant effect on trust with a coefficient value of 0.311 and influences zakat payment decisions with a coefficient value of 0.167. Trust is proven to have a significant influence on zakat payment decisions with a coefficient value of 0.265. The R-Square value for zakat payment decisions is 0.678 while the R-Square value for trust is 0.646 which indicates a strong predictive ability of the model. These findings confirm that educational content and word of mouth have an important role in shaping trust and encouraging muzakki decisions. The implications of the study recommend the need for informative and credible communication strategies to increase trust and zakat participation through formal institutions.